Effect of Music on the Efficiency of Performing a Microsurgical Arterial Anastomosis: A Prospective Randomized Study - Froschauer, Stefan M.; Holzbauer, Matthias; Kwasny, Oskar; Kastner, Philipp; Schnelzer, Richard F.; Hopfner, Meike; Duscher, Dominik (Journal of Hand and Microsurgery, 2020)
Introduction Music is commonly played in operating rooms. Because microsurgery demands utmost concentration and precise motor control, we conducted the present study to investigate a potentially beneficial impact of music on performing a microsurgical anastomosis.Materials and Methods We included a novice group (15 inexperienced medical students) and a professional group (15 experienced microsurgeons) in our study. Simple randomization was performed to allocate participants to the music-playing first or music-playing second cohort. Each participant performed two end-to-end anastomoses on a chicken thigh model. Participant demographics, their subjective preference for work environment (music/no music), and time to completion were noted. The performance of the participants was assessed using the Stanford Microsurgery and Resident Training (SMaRT) scale by an independent examiner, and the final anastomoses were evaluated according to the anastomosis lapse index.Results Listening to music had no significant effect on time to completion, SMaRT scale, and anastomosis lapse index scores in both novice and professional cohorts. However, the subjective preference to work while listening to music correlated with high SMaRT scale scores within the professional cohort (p = 0.044).Conclusion Playing their preferred music in the operating room improves the performance scores of surgeons, but only if they subjectively appreciate working with background music.
Keywords: arterial anastomosis; microsurgery; music; surgical education